Impact of Tax of Certain Banks Institutions on Financial Banks Results in Poland - Małgorzata Białas; Izabela Emerling (Communications of International Proceedings, 2022)
In recent years, characterized by dynamic development of capital and money markets and economies of many countries, there is a need to ensure greater influence on the state budget. Only increasing tax burdens can ensure these revenues. These, however, generate great social opposition, but also opposition from entities that are burdened with further tributes to the state. The implementation of the fiscal goals of the state was to be achieved through the introduction of a tax on certain financial institutions, commonly known as the bank tax. The aim of the article is to analyze how the bank tax affects the amount of financial results achieved by banks operating in Poland, as well as how banks try to minimize this burden. The main research objective of the article is to examine and compare the amount of tax on certain financial institutions paid by banks in Poland and to analyze how it affects the financial results of banks.. The basic research hypothesis is: The tax on certain financial institutions is a significant burden on the financial results of banks in Poland. The verification of the above research hypothesis is the main goal of this article. The applied research methods are based on literature studies in the analyzed area and the analysis of data from banks' financial statements in order to identify the amount of the tax burden and the factors causing its reduction. The analysis was carried out on the basis of financial data contained in the reports of selected banks in Poland in 2015-2021 and information on the condition of the banking sector in Poland published by the Polish Financial Supervision Authority.